﻿La più antica pittura nella Basilica di S. Francesco ad Assisi - Rocchi, Giuseppe (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1985)
Reconsideration of what are called the oldest extant painting fragments in the lower basilica of S. Francesco ad Assisi focuses on technical and iconographical matters. Detailed visual inspection of the fresco fragments that are found on the arco d’ingresso of the chapel of the Magdalene underscores the representation of the Madonna as the oldest section there. It leads to the suggestion that this fragment antedates even the commonly accepted earliest cycle representing the life of Francis by the Master of Saint Francis. It is proposed that this fragment may be votive and that it could have surmounted a wall tomb. This hypothesis leads to a reconsideration of the complex problem of the construction of the lower basilica and to the strong tradition of the existence of an earlier (la terza) church in which the body of the saint was initially laid to rest. In this regard, the fragments tire a vital record in unravelling the knotty problems that still beset a full evaluation of the history of the lower basilica and its pictorial decoration.